Analisis Kesalahan Berbahasa Dalam Karangan Siswa Kelas IV Sekolah Dasar - Nisa Khoerunajah; Prana Dwija Iswara; Dadan Nugraha (Jurnal Inovasi Pendidikan dan Pembelajaran Sekolah Dasar, 2024)
This research is motivated by the problems experienced by students in writing. This is based on initial observations which show that the students' writing results are not in accordance with the applicable Indonesian grammar, even though class IV students already know the functions of spelling and know the elements of complete sentences. This indicates that students' writing skills with attention to applicable grammar are still low. Based on this background, this research was conducted on the essays of class IV students at an elementary school in Kuningan Regency. This research was conducted using descriptive qualitative research methods to determine (1) spelling errors made by students, (2) morphological errors made by students, (3) syntax errors made by students. The research results obtained were that the spelling errors that were most frequently made were errors in the use of capital letters, namely 92 errors (22.16%), the most morphological errors were the use of conjunctions, 42 errors (10.12%), the most syntactic errors were ambiguous sentences, as many as 22 errors (5.30%).